Dynamics of the Spelling Process During a Copy Task: Effects of Regularity and Frequency. - Lambert, Eric; Alamargot, Denis; Larocque, Denis; Caporossi, Gilles (Canadian Journal of Experimental Psychology, 2011)
This study investigated the time course of spelling, and its influence on graphomotor execution, in a successive word copy task. According to the cascade model, these two processes may be engaged either sequentially or in parallel, depending on the cognitive demands of spelling. In this experiment, adults were asked to copy a series of words varying in frequency and spelling regularity. A combined analysis of eye and pen movements revealed periods where spelling occurred in parallel with graphomotor execution, but concerned different processing units. The extent of this parallel processing depended on the words' orthographic characteristics. Results also highlighted the specificity of word recognition for copying purposes compared with recognition for reading tasks. The results confirm the validity of the cascade model and clarify the nature of the dependence between spelling and graphomotor processes. Reprinted by permission of the publisher.